IFLANET unplugged 1999 - International Federation of Library Associations and Institutions (IFLA) ([S.l.] : SilverPlatter Information, Inc., 1998)
IFLANET'Unplugged' is a CD-ROM version of the website and contains most of the hypertext and text files that were available in the online version as of June 28, 1999
IFLA Membership Directory as a fully searchable SilverPlatter Database
System requirements: HTML or PDF format, MS DOS, Windows 3.1/95/NT, and Macintosh operating systems
Keywords: International Federation of Library Association; Library science; Library cooperation